Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1529/biophysj.106.097550
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence for the Absence of Polyproline II Stretch in the XAO Peptide

Abstract: It has been suggested that the alanine-based peptide with sequence Ac-XX-[A](7)-OO-NH(2), termed XAO where X denotes diaminobutyric acid and O denotes ornithine, exists in a predominantly polyproline-helix (P(II)) conformation in aqueous solution. In our recent work, we demonstrated that this "polyproline conformation" should be regarded as a set of local conformational states rather than as the overall conformation of the molecule. In this work, we present further evidence to support this statement. Different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 67 publications
(118 reference statements)
6
85
0
Order By: Relevance
“…Small angle x-ray studies on peptides containing significant polyproline II content (based on CD) showed a much smaller radius of gyration than expected from an extended polyproline structure [32]. Their interpretation was that polyproline II may be a folding conformation of only one or two residues in a continuous flux with other conformations and not lead to an extended semi-rigid rod structure [32]. Ma and Wang [14] also have concluded that the titin PEVK fluctuated between polyproline, beta turn, and unordered structure.…”
Section: Circular Dichroism and Pevk Secondary Structurementioning
confidence: 91%
See 1 more Smart Citation
“…Small angle x-ray studies on peptides containing significant polyproline II content (based on CD) showed a much smaller radius of gyration than expected from an extended polyproline structure [32]. Their interpretation was that polyproline II may be a folding conformation of only one or two residues in a continuous flux with other conformations and not lead to an extended semi-rigid rod structure [32]. Ma and Wang [14] also have concluded that the titin PEVK fluctuated between polyproline, beta turn, and unordered structure.…”
Section: Circular Dichroism and Pevk Secondary Structurementioning
confidence: 91%
“…Recent work [32] has suggested that the polyproline II helix may be only a temporally transient structure. Small angle x-ray studies on peptides containing significant polyproline II content (based on CD) showed a much smaller radius of gyration than expected from an extended polyproline structure [32].…”
Section: Circular Dichroism and Pevk Secondary Structurementioning
confidence: 99%
“…Scheraga and coworkers have presented evidence to challenge the previous claims of Kallenbach and others, reporting that PII is one of many conformations available to alanine in XAO and that PII is not a dominant global conformation of the XAO peptide [49,50] . Supporting this result, small angle X -ray scattering ( SAXS ) also demonstrated that the XAO peptide adopts a much smaller radius of gyration (∼ 7.4 Å ) in solution compared with that expected of an ideal, fully extended PII helix ( ∼ 13 Å ), indicating that PII bias is local and that PII helix is not a global conformation of the peptide [51] .…”
Section: Experimental Measurement Of Pii Propensitiesmentioning
confidence: 93%
“…This new tool, because it isolates the determination of structure to an individual C a , could be instrumental in discriminating between current conflicting views of the role of the P conformation in the characterization of ''unfolded'' peptides. 27,28 …”
Section: Discussionmentioning
confidence: 99%